2005
DOI: 10.1542/peds.2005-2320
|View full text |Cite
|
Sign up to set email alerts
|

Cetaphil Cleanser (Nuvo Lotion) Cures Head Lice

Abstract: outside of the traditional medical system, this means an efficient interface and bidirectional communication with community-based resources is necessary. Last, if any office-based change is to be sustained, third-party reimbursement policies should reflect the importance of these changes.We therefore praise Dr Pavan for her participation in an important learning collaborative. With equally laudable efforts in lobbying for fair reimbursement strategies and pursuing community-specific efforts around the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…63 The study was criticized for being uncontrolled, with no blinding, randomization, or comparison group. 64 The lotion used in the study was later identified as Cetaphil cleanser [Galderma Laboratories, Fort Worth, TX], 65 and instructions for its use are available on the Internet. 66 It has not been approved by the FDA for use as a pediculicide.…”
Section: Occlusive Agentsmentioning
confidence: 99%
“…63 The study was criticized for being uncontrolled, with no blinding, randomization, or comparison group. 64 The lotion used in the study was later identified as Cetaphil cleanser [Galderma Laboratories, Fort Worth, TX], 65 and instructions for its use are available on the Internet. 66 It has not been approved by the FDA for use as a pediculicide.…”
Section: Occlusive Agentsmentioning
confidence: 99%
“…Recent articles in the peer-reviewed literature, the risk management evaluation of Lindane the POPs Reviewing Committee (UNEP 2007a) and a summary documentation of the International POPs Elimination Network (IPEN 2009) have documented the safe, efficacious use of alternatives to Lindane for treatment of head lice, including hot air treatments (Goates 2006), wet combing, cetaphil cleanser and dimethicone lotion (Pearlman 2005). The efficacy of these alternatives matched or exceeded that of Lindane without the development of resistance or toxic effects in the patient.…”
Section: Substitution Of Lindane For the Permitted Exempted Uses (Licmentioning
confidence: 99%
“…2 The AAP recommendation that young children be imaged with ultrasound and voiding cystourethrography after a first febrile urinary tract infection was based on evidence that was generously labeled as "fair" at the time. 4 More recently, Roberts indicated that the imaging recommendations should be reconsidered. 4 More recently, Roberts indicated that the imaging recommendations should be reconsidered.…”
Section: Evidence Does Not Support American Academy Of Pediatrics Recmentioning
confidence: 99%